Telecommunications law and regulation in Nigeria : a study of universal service provision - Opata, Chukwudiebube Bede Abraham (2010)
This thesis undertakes an analysis of the law pertaining to the regulation of telecommunications in Nigeria generally and more specifically with regards to the extension of access to telecommunications services to unserved and underserved persons and areas in Nigeria. The study is situated in the context of privatisation and liberalisation reform of the Nigerian telecommunications sector. It addresses the question of how to extend access to telecommunications services in Nigeria to unserved and underserved persons and areas. This question is researched by focusing on the sector regulator the Nigerian Communications Commission and analysing the mechanisms, ranging from licensing to interconnection to universal service provision and the National Rural Telecommunication Programme, that have been deployed in the past to achieve this objective to ascertain how these may be improved to ensure that as many persons and areas as possible have access to telecommunications services. The issue of securing the accountability of the regulator responsible for the deployment of these access extension mechanisms is also addressed. The research identifies the main international influences on the development of the Nigerian regulatory framework and shows the country’s ability to borrow from a number of sources while adapting and refining the borrowed rules to solve Nigerian problems. The thesis makes a contribution to knowledge in at least three material ways. It is, to the best of my knowledge, the first work on the legal framework for the regulation of telecommunications in Nigeria after the enactment of the Communications Act 2003. Secondly, it is also the first work that I am aware of which analyses issues of access to telecommunications services using a variety of regulatory mechanism as opposed to focusing on universal access and universal service alone. Finally it presents a positive illustration of a successful outcome of globalisation of rules, specifically the transposition or transplantation of specific legal rules in the economic context of a developing African country.